Let's hear it for Almigal - Kupfer, Wendy (Delray Beach, Fl. : Handfinger Press, 2012)
Meet Almigal, a spunky little girl with a BIG personality who's determined to hear "every single sound in the whole entire universe!" That includes ... her friend Isabella's baby brother's funny giggle, the robins singing outside her bedroom window, the soft Swan Song Madam plays during ballet class, and especially her friend Chloe's teeny-tiny voice. But most of all, Almigal wants to hear her Mommy and Daddy whisper, "We love you, Almigal!" when they tuck her into bed at night. Almigal's spirit and her cotton-candy pink cochlear implants will have everyone shouting, "Let's hear it for Almigal!"
Keywords: Hard of hearing children -- Juvenile fiction; Deafness in children -- Juvenile fiction; Cochlear implants -- Juvenile fiction; Deaf people -- Fiction; Deafness -- Fiction; Hearing -- Fiction; Hearing disorders -- Fiction; People with disabilities -- Fiction; Ear -- Diseases; Cochlear implants; Deafness in children; Hearing impaired children; Fiction; Juvenile works